Does MCT1-T1470A Polymorphism Modify Lactate Kinetics and Training Status? - Turgay, Faruk; Bilgin, Zafer; Yigittürk, Oya; Durmaz, Burak; Aşıkovalı, Semih; Köksal, Ahmet (Progress in Nutrition, 2021)
Study Objectives: The (MCT1-T1470A) polymorphism related to monocarboxylate transporters 1 (MCTs) which transport lactate (LA) may affect LA kinetics and training status, which is unclear. Methods: Participants in the athletic group (AG; 42 anaerobic athletes; 21.8 ± 2.7 years) and the control group (CG; 39 sedentary men; 23.0 ± 3.3 years) performed the Yoyo recovery level 1 test. LA elimination speeds were calculated by dividing the difference between LA5, LA15, and LA30 values of passive recovery corresponding to the 5th, 15th, and 30th minutes following the Yoyo test by the elapsed time. MCT1 polymorphism was determined from genomic DNA samples by next-generation sequencing. Results:The LA5, LA15, and LA30 values of the control group were significantly higher than those of the athlete group (p=0.053, p=0.042, and p=0.028, respectively), but not for LA elimination speeds. There was no significant difference for these parameters between genotype groups. Although the VO2max of the AA control group was significantly greater than that of the T carrier (Tc) control group, there was no significant difference for VO2max between the athletic genotype groups (AA and Tc). Conclusions: MCT1-T1470A polymorphism did not have a significant effect on LA kinetics in athletes. However, the AA group was negatively affected for VO2max compared to the Tc group. This may be due to extreme sensitivity of the AA group to the training caused by this polymorphism. Further studies are needed to shed light on this entity.